2021
DOI: 10.2147/jmdh.s293601
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR Combined with CT Examination in the Diagnosis and Prognosis Evaluation of COVID-19 Patients in Fangcang Hospital: A Case Series

Abstract: Rationale: Currently, the "gold standard" is real-time reverse transcriptase-polymerase chain reaction (RT-PCR) amplification of the viral DNA for diagnosis of COVID-19 infection. However, early reports of test performance in the Wuhan outbreak showed variable sensitivities. Therefore, the simple use of RT-PCR as a discharge standard for COVID-19 patients may be risky. Early discussions suggested that CT should be the preferred modality for the diagnosis of COVID-19. However, the use of CT for COVID-19 dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…2020–532). 2 All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1975, as revised in 2008. Because of its retrospective and emergent nature and evaluation of the imaging and clinical data of the patients, the study involved no potential risk, and verbal informed consent was obtained from all patients to be included regarding publication of the case details, and our IRB approved the informed verbal consent process.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…2020–532). 2 All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1975, as revised in 2008. Because of its retrospective and emergent nature and evaluation of the imaging and clinical data of the patients, the study involved no potential risk, and verbal informed consent was obtained from all patients to be included regarding publication of the case details, and our IRB approved the informed verbal consent process.…”
Section: Methodsmentioning
confidence: 99%
“…On December 8, 2019, it was confirmed that several patients with pneumonia caused by unknown causes were infected with the new coronavirus, which has not been detected in humans or animals before. 1 , 2 On February 11, 2020, the WHO named this novel virus “COVID-19” (Coronavirus disease 2019). Since then, the WHO emergency committee has declared COVID-19 as a global health emergency with more than 200 countries reporting COVID-19 cases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations